Quality of Higher Education and the Labor Market in Developing Countries: Evidence from an Education Reform in Senegal. (October 2015) - Boccanfuso, Dorothée; Larouche, Alexandre; Trandafir, Mircea
Highlights: We study the link between quality of higher education and labor market. We exploit an education reform in Senegal focused on quality improvement before 2005. Quality improvements have positive effects on employment of young college graduates. After reform, new university graduates are more likely to work in the public sector. Reform likely narrowed gap between quality of high-skill labor demanded and supplied. Summary: While many studies examine the effect of primary education quality on labor market outcomes in developing countries, little is known about the effects at higher levels. We exploit the quasi-experiment provided by a large-scale education reform launched in Senegal in 2000 to investigate how quality improvements at the university level affect employment. Our difference-in-difference estimates suggest that young high-skilled workers experienced a nine percentage-point employment gain relative to older workers. They are also more likely to have "better" jobs (in the service industry or government), suggesting a reduction in the mismatch between the quality of high-skilled labor demanded and supplied.